Effects of diagenesis on quality of dengying formation deep dolomite reservoir, Central Sichuan Basin, China: Insights from petrology, geochemistry and in situ U-Pb dating - Gu, Yifan; Wang, Zhanlei; Yang, Changcheng; Luo, Mingsheng; Jiang, Yuqiang; Luo, Xiaorong; Zhou, Lu; Wang, Haijun (Frontiers in Earth Science, 2023)
The Ediacaran Dengying Formation in Central Sichuan Basin is the deep dolomite gas reservoir with the largest natural gas reserves in China, providing an excellent example for understanding the effect of diagenesis evolution on deep dolomite reservoir quality. By integrating petrology, geochemistry and in situ U-Pb dating, this study aims to reveal the genesis of different rock fabrics and their corresponding diagenetic events, and to discuss the temporal relationship of diagenetic events and their effects on the reservoir quality of Dengying Formation. Two phases of dolomite and three phases of dolomite cement are identified in Ediacaran Dengying Formation deep dolomite reservoirs of Central Sichuan Basin as follows: (1) matrix dolomites (MD), (2) fine-medium crystalline dolomites (FMD), (3) fibrous dolomites (FD), (4) medium-coarse crystalline dolomites (MCD), and (5) saddle dolomite (SD). By analyzing petrographic and temporal relationships between these fabrics, it is suggested that the deep dolomite reservoir of Dengying Formation in Central Sichuan Basin has experienced six diagenetic stages, including (1) syndiagenetic stage, (2) the first-time early diagenetic stage, (3) epidiagenetic stage, (4) the second-time early diagenetic stage, (5) middle diagenetic stage and (6) late diagenetic stage. Microbial dolomitization during syndiagenetic stage has limited increase in reservoir porosity, but it is of great significance for preservation of reservoir spaces. Silicification is the most unfavorable for reservoir formation, but its the duration and influence range are very limited. At epidiagenetic stage, the physical properties of Dengying Formation dolomite reservoir have been greatly improved. Two-time early diagenetic stages are both destructive for preservation of reservoir spaces. During middle diagenetic stage, two-stage of hydrothermal alterations occurred, corresponding to Late Silurian to Devonian and Late Permian, respectively. Hydrothermal alteration of the MD is both constructive and destructive, but overall it is constructive, but the improvement of physical properties is limited. In terms of the karstified MD, both two-stage hydrothermal alterations were destructive, resulting in damage of reservoir physical properties caused by cementation of two-stage SD and one-stage MVT minerals.